2020
DOI: 10.3389/fmicb.2020.585140
|View full text |Cite
|
Sign up to set email alerts
|

Protein Residues and a Novel Motif Involved in the Cellular Localization of CheZ in Azorhizobium caulinodans ORS571

Abstract: Chemotaxis is essential for the competitiveness of motile bacteria in complex and harsh environments. The localization of chemotactic proteins in the cell is critical for coordinating a maximal response to chemotactic signals. One chemotaxis protein with a well-defined subcellular localization is the phosphatase CheZ. CheZ localizes to cell poles by binding with CheA in Escherichia coli and other enteric bacteria, or binding with a poorly understood protein called ChePep in epsilon-Proteobacteria. In alpha-Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…In this study, we determined CheZ localizes to the poles upon inhibiting the electron transport chain of A. caulinodans, which requires the C-terminus of CheZ and one of the conserved phosphatase active site, D165 but not Q169. These results are consistent with our previous observation that the substitution mutant of CheZ (CheZD165A) showed a low level of localization, while the localization pattern of CheZQ169A was similar to wild-type CheZ (Liu et al, 2020). Recently, we identified that a novel motif AXXF(Y)Q, which is adjacent to the phosphatase active sites, controls the polar localization of CheZ (Liu et al, 2020), and we presumed the role of D165 of CheZ on localization might be achieved by interacting with the motif.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, we determined CheZ localizes to the poles upon inhibiting the electron transport chain of A. caulinodans, which requires the C-terminus of CheZ and one of the conserved phosphatase active site, D165 but not Q169. These results are consistent with our previous observation that the substitution mutant of CheZ (CheZD165A) showed a low level of localization, while the localization pattern of CheZQ169A was similar to wild-type CheZ (Liu et al, 2020). Recently, we identified that a novel motif AXXF(Y)Q, which is adjacent to the phosphatase active sites, controls the polar localization of CheZ (Liu et al, 2020), and we presumed the role of D165 of CheZ on localization might be achieved by interacting with the motif.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the polar localization of chemotaxis proteins improves the cooperative interactions between them, which enables bacteria sense nanomolar concentrations of signal molecules over a wide range (Greenfield et al, 2009). We previously identified the residues and domains of CheZ, which are important for the cellular localization of CheZ (Liu et al, 2020). In this study, we further found that the location of CheZ can be regulated by hypoxia.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations